Diversity and abundance of insect visitors of karonda (Carissa carandas) flowers under Hisar conditions - ANOOSHA, VADDE; SAINI, SUMIT; YADAV, SUNITA; KAUSHIK, H D (The Indian Journal of Agricultural Sciences, 2018)
Studies conducted during 2014-15 revealed that karonda (Carissa carandas L.)flowers attracted wide variety of insect species belonging to 4 orders, 8 families, 12 genera and 15 species. Among them eight belonging to order Hymenoptera, four to Lepidoptera, two to Diptera and one to Coleoptera. Among all these insects, Papilio demoleus, Helicoverpa armigera, Apis florea and Polistes olivaceus were the dominant flower visitors. The other important insects visiting karonda flowers were Delta esuriens and Eurema hecabe, the latter group of insects mostly visited flowers at interrupted hours and not considered as the reliable pollinators. Peak abundance of major insect visitors recorded during mid - day hours as compared to morning and evening hours.